Pengaruh konsentrasi IAA (Indole Acetic Acid) dan BAP (Benzil Amino Purin) terhadap pertumbuhan awal sambung samping Jambu Biji (Psidium guajava) Var. Kristal - Hendra Pratomo; Karno Karno; Budi Adi Kristanto (Journal of Agro Complex, 2018)
The purpose of this research was to study the influence of various concentrations of IAA and BAP on early growth budding of guava (Psidium guajava L.) Var. Kristal in side grafting propagation method. The experiment used completely randomized factorial design. The first factor was various concentrations of IAA (0, 100, and 200 ppm) and the second factor was various concentrations of BAP (0, 100, and 200 ppm). Each treatment was repeated three times. Parameters observed were the time of bud break, time of shoot emergence, and shoot length. The data were analyzed by variance and continued analyzed by Duncan Multiple Range Test. The results showed that the level of IAA concentration gave effect (P<0,05) to time of shoot emergence and shoot length. Level of BAP concentrations gave significant effect (P<0,05) to the time of bud break, time of shoot emergence, and shoot length. The interaction between the concentration level of IAA and BAP had significant effect (P<0,05) on the time of bud break, time of shoot emergence and shoot length. Keywords : Guava, Psidium guajava, Side Grafting, IAA, BAP.